2020
DOI: 10.1017/s1041610220004081
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 public health restrictions on older people in Uganda: “hunger is really one of those problems brought by this COVID”

Abstract: Objectives: To explore the impact of COVID-19 related public health restrictions on the lives of older adults living in Uganda. Design: Qualitative semi-structured interview study Setting: Participants’ homes Participants: Older adults living in Uganda (aged 60+) Measurements: Older adults in Uganda were interviewed over the phone and asked about their lives before and since COVID-19, and how public health restrictions have affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 18 publications
0
36
1
Order By: Relevance
“…Five studies exclusively reported on changes in dietary behaviors in older individuals [ 12 , 18 , 26 , 27 , 31 ], 17 exclusively reported on changes in physical activity [ 13 - 17 , 19 , 22 , 23 , 25 , 28 - 30 , 33 - 35 , 37 , 38 ], and 5 reported on both [ 20 , 21 , 24 , 32 , 36 ]. Many (n = 17) studies reported on a variety of diet and/or physical activity outcomes for the total study population but provided only selective results for the specified age group of 50+ years [ 12 , 14 , 16 , 17 , 19 - 25 , 27 , 29 , 31 , 32 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies exclusively reported on changes in dietary behaviors in older individuals [ 12 , 18 , 26 , 27 , 31 ], 17 exclusively reported on changes in physical activity [ 13 - 17 , 19 , 22 , 23 , 25 , 28 - 30 , 33 - 35 , 37 , 38 ], and 5 reported on both [ 20 , 21 , 24 , 32 , 36 ]. Many (n = 17) studies reported on a variety of diet and/or physical activity outcomes for the total study population but provided only selective results for the specified age group of 50+ years [ 12 , 14 , 16 , 17 , 19 - 25 , 27 , 29 , 31 , 32 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing the 2019 novel coronavirus disease (COVID- 19) pandemic and the mechanisms determining the cause of COVID-19 are under medical research worldwide [1]; equally, the psychosocial consequences of the restrictions are also the subject of research. To date, studies have mostly addressed adults and older adults [2][3][4] but informal caregivers have rarely been subject to current pandemic research. An informal caregiver is a person who has a significant personal relationship with, and provides a broad range of assistance for, a person in need of care.…”
Section: Introductionmentioning
confidence: 99%
“…One, compared to middle-aged adults who are more likely to be economically active, elderly individuals are less likely to be involved in income-generating activities to be able to cushion themselves against the indirect effects of COVID-19 mitigation measures but rather depend on others. This position is corroborated by findings of a study from Uganda that showed that older people (above 60 years), among other things, lacked access to enough food, lost the little income generated from selling farm produce and could not access healthcare or interact with family and friends due to the COVID-19 regulations (25). Two, married women or women, in general, are more likely to be vulnerable to the indirect COVID-19 mitigation measures because compared to men, they are less likely to be employed, take on unpaid care burden for children and other household chores, depend on their male partners and are more at risk of experiencing gender-based violence, especially when employment or income is lost (37)(38)(39).…”
Section: Discussionmentioning
confidence: 70%
“…Multicollinearity of the independent variables was assessed using variance inflation factors. The dependent variable was the disruption index (continuous variable), while the selection of independent variables was informed by factors that have been suggested in the literature to determine individuals' vulnerability to COVID-19 mitigation measures (7,19,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%